2014
DOI: 10.1111/phpp.12097
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Kaempferia parviflora extract on UVB‐induced skin photoaging in hairless mice

Abstract: The results show that oral administration of KPE significantly prevents UVB-induced photoaging in hairless mice, suggesting its potential as a natural antiphotoaging material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 20 publications
2
59
0
Order By: Relevance
“…To visualize the changes in dermal collagen fibers after UVB exposure, histological analysis were performed. The decreases of dermal collagen fibers in UVB‐exposed mice skin have been reported . As with many previous studies, our data showed a decrease in the abundance and density of dermal collagen fibers in mice exposed to UVB (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…To visualize the changes in dermal collagen fibers after UVB exposure, histological analysis were performed. The decreases of dermal collagen fibers in UVB‐exposed mice skin have been reported . As with many previous studies, our data showed a decrease in the abundance and density of dermal collagen fibers in mice exposed to UVB (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…MMPs are play pivotal roles in tumor invasion, inflammation, and skin aging [9,10]. Additionally, UVB induces the expression of the cytokines interleukin (IL)-1, tumor necrosis factor (TNF)-a, and IL-6 in keratinocytes [9,11,12]. Inflammatory mediators induced by ROS, together with these cytokines may contribute to many acute and chronic photo-damage disorders, including sunburn, hyperpigmentation, aging and carcinogenesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…MAPK family member activation leads to the increased expression of the transcription factor activator protein-1 (AP-1) and nuclear factor-kappa (NF-jB), which in turn results in the upregulation of matrix metalloproteinases (MMPs). MMPs are play pivotal roles in tumor invasion, inflammation, and skin aging [9,10]. Additionally, UVB induces the expression of the cytokines interleukin (IL)-1, tumor necrosis factor (TNF)-a, and IL-6 in keratinocytes [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes include collagenase-1 (MMP-1) and collagenase-3 (MMP-13), which are the primary mediators of connective tissue damage in skin following UV irradiation exposure (Ravanti et al 1999;Brennan et al 2003;Ahn et al 2012). It has been proposed that inhibition of these enzymes might be a useful strategy for preventing UV-accelerated skin ageing by restoring the balance between collagen degradation and synthesis (Brennan et al 2003;Ahn et al 2012;Itsarasook et al 2014;Park et al 2014).…”
Section: Introductionmentioning
confidence: 99%